Relationship Between Waist Circumference and Body Mass Index with HbA1c Levels in Patients with Type 2 Diabetes Mellitus - Sukma Febriani; Ismatul Fauziah Rambe; Shahrul Rahman; Ren Astrid Allail Siregar (Jurnal Kesehatan dan Kedokteran, 2026)
Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder characterized by persistent hyperglycemia and complex pathophysiological mechanisms. Obesity, assessed through Body Mass Index (BMI) and waist circumference (WC), is commonly associated with poor glycemic control, yet previous studies have reported inconsistent findings. Objective: This study aimed to analyze the relationship between waist circumference and BMI with HbA1c levels in patients with T2DM at Haji General Hospital Medan. Methods: A quantitative analytical study with a cross-sectional design was conducted involving 48 patients with T2DM who met the inclusion criteria. Anthropometric data, including BMI and WC, were measured directly, while HbA1c values were obtained from medical records. Bivariate analysis was performed using the Spearman correlation test, and multivariate analysis was conducted using ordinal logistic regression. Results: The analysis showed no significant association between waist circumference and HbA1c levels (r = −0.141; p = 0.339) or between BMI and HbA1c levels (r = 0.075; p = 0.611). Multivariate analysis also indicated that BMI and WC simultaneously did not significantly affect HbA1c categories (p > 0.05). Implications: These findings suggest that glycemic control in T2DM patients is influenced by multifactorial mechanisms beyond anthropometric parameters, highlighting the importance of considering behavioral, clinical, and therapeutic factors in diabetes management. Originality: This study provides context-specific evidence by simultaneously evaluating BMI and WC in a clinical outpatient population, contributing to the ongoing debate regarding the relevance of simple anthropometric indicators in predicting glycemic control.